Decadal increase in Ningaloo Niño since the late 1990s. Issue 1 (5th January 2015) - Feng, Ming; Hendon, Harry H.; Xie, Shang‐Ping; Marshall, Andrew G.; Schiller, Andreas; Kosaka, Yu; Caputi, Nick; Pearce, Alan
Abstract Ningaloo Niño refers to the episodic occurrence of anomalously warm ocean conditions along the subtropical coast of Western Australia (WA). Ningaloo Niño typically develops in austral spring, peaks in summer, and decays in autumn, and it often occurs in conjunction with La Niña conditions in the Pacific which promote poleward transport of warm tropical waters by the Leeuwin Current. Since the late 1990s, there has been a marked increase in the occurrence of Ningaloo Niño, which is likely related to the recent swing to the negative phase of the Interdecadal Pacific Oscillation (IPO) and enhanced El Niño–Southern Oscillation variance since 1970s. The swing to the negative IPO sustains positive heat content anomalies and initiates more frequent cyclonic wind anomalies off the WA coast so favoring enhanced poleward heat transport by the Leeuwin Current. The anthropogenically forced global warming has made it easier for natural variability to drive extreme ocean temperatures in the region.